The Big Five Personality Traits and Earnings: A Meta-Analysis - Giammarco Alderotti; Chiara Rapallini; Silvio Traverso (Global Labor Organization (GLO), 2021)
The past two decades have witnessed an increasing interest in the relationship between personality and labor market outcomes, as well as the emergence of the Five-Factor Model as the reference framework for the study of personality. In this paper, we provide the first meta-analytical review of the empirical literature on the association between personal earnings and the Big Five personality traits. The analysis combines the results of 65 peer-reviewed articles published between 2001-2020, from which we retrieved 936 partial effect sizes. Overall, the primary literature provides robust support for a positive association between personal earnings and the traits of Openness, Conscientiousness, and Extraversion, while simultaneously revealing a negative and significant association between earnings and the traits of Agreeableness and Neuroticism. We find no evidence of a substantial publication bias. Meta-regression estimates suggest that Openness and Conscientiousness are positively associated with earnings even when primary researchers control for individual cognitive abilities and educational attainments. Similarly, the studies that includes labor market control variables exhibit weaker associations between earnings and Extraversion and Agreeableness. The results of the primary studies seem unaffected by the time at which the Big Five are measured, as well as by the scale and number of inventory items. Meta-regression estimates suggest that the results of the primary literature are not stable across cultures and gender, and that the ranking and academic field of the journal matter.
Keywords: J24; D91; 330; Big Five personality traits; earnings; meta-analysis